Soybean grown in lowland rice areas to reduce weed infestation Cultivo de soja em área de arroz irrigado para reduzir a infestação de plantas daninhas - Cardoso F.C.* (2024)
© 2024, Departamento de Engenharia Agricola - UFCG/Cnpq. All rights reserved.Lowland rice in Santa Catarina (SC), Brazil, is grown as a sole crop, which has aggravated problems with weeds. In this context, the objective of this study was to evaluate the efficacy of weed management systems in soybean crops to decrease weed infestation in lowland rice production areas, using pre-and post-emergence herbicides. The experiment was conducted in Turvo, SC, from August 2021 to April 2022. A randomized block design with four replications was used, in a 6 × 5 factorial arrangement. The factors consisted of six pre-emergence herbicides treatments (S-metolachlor, diclosulam, sulfentrazone, sulfentrazone + diuron, pyroxasulfone + flumioxazin, and a control without herbicide), and five post-emergence herbicide treatments: control without herbicide, glyphosate at two rates (930 and 1,550 g a.e. ha-1), applied alone or in combination with clethodim. The herbicide sulfentrazone caused persistent phytotoxicity and resulted in the lowest soybean grain yield. The herbicide S-metolachlor was ineffective in controlling weed species, except barnyard grass, even when combined with post-emergence application. The poor control of these weed species does not result in significant interference, causing no significant decreases in grain yield of soybean crops grown in floodplain soils. The use of S-metolachlor, diclosulam, and pyroxasulfone + flumioxazin, combined with post-emergence application of glyphosate (930 g a.e. ha-1), resulted in highly effective control of barnyard grass, inhibiting weed seed production. Only the combination of glyphosate (1,550 g a.e. ha-1) with clethodim can suppress barnyard grass seed production without using pre-emergence herbicides.